2004
DOI: 10.1186/1743-422x-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Persistent expression of chemokine and chemokine receptor RNAs at primary and latent sites of herpes simplex virus 1 infection

Abstract: Inflammatory cytokines and infiltrating T cells are readily detected in herpes simplex virus (HSV) infected mouse cornea and trigeminal ganglia (TG) during the acute phase of infection, and certain cytokines continue to be expressed at lower levels in infected TG during the subsequent latent phase. Recent results have shown that HSV infection activates Toll-like receptor signaling. Thus, we hypothesized that chemokines may be broadly expressed at both primary sites and latent sites of HSV infection for prolong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“… 65 Of note, several studies report CXCL12 expression to be very low in steady-state, increasing following inflammation/damage. 39 , 61 , 63 , 65 Our data are in accordance with these reports, where the levels of CXCL12 expression in the corneal epithelium and stroma increased following suture placement.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 65 Of note, several studies report CXCL12 expression to be very low in steady-state, increasing following inflammation/damage. 39 , 61 , 63 , 65 Our data are in accordance with these reports, where the levels of CXCL12 expression in the corneal epithelium and stroma increased following suture placement.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the similarity of the “induction ratio” (relative expression in HSV-infected/relative expression in sham-infected cornea) to that of the other chemokine receptors reported in their paper is interesting to note, as it indicates an increase in CXCR4 following scarification in the sham group. 61 Our results revealed that approximately 60% of steady-state cDCs in the naïve cornea were CXCR4 positive. This percentage decreased to an average of 35% of total cDCs following suture placement.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This control most likely occurs through the production of cytokines such as IFN gamma, especially in the trigeminal ganglia [19,24,25]. IFN gamma is produced mainly by T lymphocytes [26], and one of its major actions is to increase iNOS and ROS production for killing pathogens [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…DCs can be recruited to the lungs and in the cornea of the eye, where they contribute to host defense (8,9). Studies have shown that diphtheria toxin (DT)-induced depletion of DCs in CD11c-DTR mice (in which the DT receptor [DTR] is expressed under the control of the CD11c promoter) inhibited the migration of natural killer cells and neutrophils to locally infected cornea, resulting in severe pathology (10,11).…”
mentioning
confidence: 99%